ITEGRASI SAINS DAN AGAMA DALAM PENANAMAN KARAKTER PEDULI LINGKUNGAN SISWA SDIT ALAM NURUL DUA NGAWI - Fatimatul Asroriah; Darmanto (AL IBTIDAIYAH: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
The persistent challenge of environmental degradation necessitates educational interventions that foster pro-environmental values from an early age. This study addresses a critical gap by investigating how Integrated Islamic Elementary Schools (SDIT), which uniquely blend scientific and religious curricula, can effectively cultivate environmental stewardship. Employing a descriptive qualitative methodology at SDIT Alam Nurul Islam Dua Ngawi, data was gathered via observation, in-depth interviews, and document analysis. The findings reveal that contextual, nature-based learning which explicitly links scientific concepts (e.g., ecosystems, conservation) with Qur'anic principles and the ethos of khalifah fil ardh successfully fosters students' environmental awareness, responsible attitudes, and sustainable habits. The integration establishes a dual reinforcement mechanism, where environmental understanding is concurrently framed as both a scientific imperative and a moral-spiritual obligation, leading to deeper value internalization. This research proposes an integrative learning model as a sustainable strategy for character and environmental education in Islamic primary institutions